1996
DOI: 10.1128/mcb.16.5.2002
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Circles of Heterogeneous Sizes in Carcinogen-Treated Cells: Two-Dimensional Gel Analysis of Circular DNA Molecules

Abstract: Extrachromosomal circular DNA molecules are associated with genomic instability, and circles containing inverted repeats were suggested to be the early amplification products. Here we present for the first time the use of neutral-neutral two-dimensional (2D) gel electrophoresis as a technique for the identification, isolation, and characterization of heterogeneous populations of circular molecules. Using this technique, we demonstrated that in N-methyl-N'-nitro-N-nitrosoguanidine-treated simian virus 40-transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(113 citation statements)
references
References 77 publications
(118 reference statements)
3
110
0
Order By: Relevance
“…Those analyses were performed with DNA of patients with genetic diseases, for example Fanconi's anemia, in comparison with DNA of normal skin fibroblasts (1,3). Other reports have shown that the elevated amount of spcDNA was apparently connected with increased aging (17,18) and with transformation of cells (1,4,15). Until now there is only one report that directly compares the spcDNA of normal skin fibroblasts with those of a colon carcinoma tissue and of the tumor cell line HeLa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those analyses were performed with DNA of patients with genetic diseases, for example Fanconi's anemia, in comparison with DNA of normal skin fibroblasts (1,3). Other reports have shown that the elevated amount of spcDNA was apparently connected with increased aging (17,18) and with transformation of cells (1,4,15). Until now there is only one report that directly compares the spcDNA of normal skin fibroblasts with those of a colon carcinoma tissue and of the tumor cell line HeLa.…”
Section: Discussionmentioning
confidence: 99%
“…By this technique, DNA molecules are separated both according to their size and their structure. Therefore, a population of molecules that are of the same structure, but of heterogeneous molecular mass, generates a continuous arc (1,15). The structural identity of the DNA in each arc can be determined by electron microscopy (15) and verified by molecular techniques (6,7,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved by analyzing telomeric DNA using neutral-neutral 2D gel electrophoresis, which separates telomeric restriction fragments first by size and then by shape. 20,21 The knockdown of BRCA1 by BRCA1 siRNA in MCF-7 cells has been described previously. 5 The results presented are the mean and standard error from three independent experiments.…”
Section: Dna Damage Response Is Independent Of Pten Statusmentioning
confidence: 99%
“…spcDNAs can also be induced or increased by DNA damaging agents (Cohen and Lavi 1996;Cohen et al, 1997) and inhibitors of DNA synthesis, including the common fragile site inducer aphidicolin (Sunnerhagen et al, 1989). The presence of sequences with considerable homology to spcDNA right in the middle of two of the common fragile sites may therefore not be coincidental.…”
Section: Discussionmentioning
confidence: 99%